Methodological Approaches to Societies in Transformation How to Make Sense of Change - Berriane, Yasmine; Derks, Annuska; Kreil, Aymon; Lüddeckens, Dorothea (Anthropology, Change, and Development, 2021)
This open access book provides methodological devices and analytical frameworks for the study of societies in transformation. It explores a central paradox in the study of change: making sense of change requires long-term perspectives on societal transformations and on the different ways people experience social change, whereas the research carried out to study change is necessarily limited to a relatively short space of time. This volume offers a range of methodological responses to this challenge by paying attention to the complex entanglement of qualitative research and the metanarratives generally used to account for change. Each chapter is based on a concrete case study from different parts of the world and tackles a diversity of topics, analytical approaches, and data collection methods. The contributors' innovative solutions provide valuable tools and techniques for all those interested in the study of change.